The strange polarimetric behavior of Asteroid (234) Barbara - Cellino, Alberto (2006)
We have discovered that the Asteroid (234) Barbara exhibits very anomalous polarimetric properties. The phase-polarization curve of this asteroid is unique and is not matched by any other known atmosphereless body of our Solar System. Although a few preliminary conjectures can be made, for the moment the reasons of the peculiar polarimetric properties of this asteroid remain essentially unknown.